A study into the long-overlooked carcinogenic radon in bottled water and deep well water in Dhaka, Bangladesh - Mahmud, Jubair Al; Siraz, M. M. Mahfuz; Alam, Mohammad Shafiqul; Das, Sudeb Chandra; Bradley, D.A. *; Khandaker, Mayeen Uddin *; Tokonami, Shinji; Shelley, Afroza; Yeasmin, Selina (Taylor and Francis Group, 2023)
Radon (222Rn), a radioactive and gaseous progeny of Uranium (238U) decay series, accounts for almost 50% of the total background radiation in our dwelling environment. Inhalation and ingestion of radon in excessive amounts pose serious health effects to humans. The first-ever measurement of radon concentration in commercial bottled water available in Dhaka city and deep well water samples from the campus of the University of Dhaka was carried out using the RAD7 Radon monitoring system. The concentration of radon in the bottled water ranged from 0.11 Bq/L to 1.30 Bq/L with a mean of 0.59 Bq/L, and the deep well water showed a mean of 4.88 Bq/L with a range of 3.02 Bq/L to 5.98 Bq/L. All twenty-five samples of water had radon concentrations within the recommended limits of USEPA and WHO. The mean annual effective doses from radon in bottled water and deep well water were evaluated to be 0.126 μSv/y and 12.481 μSv/y, respectively. Although the calculated doses indicate the least potential risk according to WHO and UNSCEAR, however, it is expected that the present results play an important role in setting up a national guideline for radon in drinking water, and the monitoring of radon for the safety of public health.